Towards Effective Development of Web-based Business Applications - Abdul-Aziz, Azlianor; Koronios, Andy; Gao, Jing; Sulong, Muhammad Suhaizan (IBIMA Publishing, 2012)
The Internet and the Web continue to evolve at a rapid pace where the Internet as the medium for the Web to provide and share information to global users without boundaries. This has caused the information systems change from standalone desktops to networked systems in order to effectively utilise the Web-specific characteristics for easy access to information anywhere. For this reason, the development of such information systems particularly the e-business applications would need to change from traditional development method via software development life cycle to new development methodology through web development life cycle. This new development methodology has been widely used and recognised due to its focus on developing business applications reflecting the nature of the Web. This paper presents a comprehensive review of related literature in which the web development life cycle that considers the unique and special requirements of developing web-based applications with success factors, is more effective compared to the traditional software development. The review findings are taken as a basis for conducting case studies to investigate any issues and challenges from the perspective of web development team.